2016
DOI: 10.1590/1807-3107bor-2016.vol30.0118
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of the clinical behavior of oral hairy leukoplakia in 215 HIV-seropositive patients

Abstract: Oral manifestations are common findings in human immunodeficiency virus (HIV) infected patients and frequently influence the overall health. Oral hairy leukoplakia (OHL) is strongly associated with HIV infection demonstrating its relationship with the individual's immune status and progression of immunosuppression. This study aims to retrospectively evaluate OHL in HIV patients, analyzing its incidence, demographic aspects and possible changes in clinical and epidemiological profile of the disease over 17 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 24 publications
0
12
0
4
Order By: Relevance
“…Pode-se citar também a leucoplasia pilosa oral como uma manifestação oral decorrente da infecção por EBV. A doença apresenta-se como uma lesão assintomática, encontrada principalmente em pacientes imunossuprimidos (VALE et al, 2016). É clinicamente caracterizada por placas brancas elevadas (GUIDRY et al, 2017), de aparência felpuda ou ondulada (GREENSPAN et al, 2016), não removíveis por raspagem e localizadas principalmente em borda lateral de língua, podendo ocorrer bilateralmente (VALE et al, 2016).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Pode-se citar também a leucoplasia pilosa oral como uma manifestação oral decorrente da infecção por EBV. A doença apresenta-se como uma lesão assintomática, encontrada principalmente em pacientes imunossuprimidos (VALE et al, 2016). É clinicamente caracterizada por placas brancas elevadas (GUIDRY et al, 2017), de aparência felpuda ou ondulada (GREENSPAN et al, 2016), não removíveis por raspagem e localizadas principalmente em borda lateral de língua, podendo ocorrer bilateralmente (VALE et al, 2016).…”
Section: Discussionunclassified
“…A doença apresenta-se como uma lesão assintomática, encontrada principalmente em pacientes imunossuprimidos (VALE et al, 2016). É clinicamente caracterizada por placas brancas elevadas (GUIDRY et al, 2017), de aparência felpuda ou ondulada (GREENSPAN et al, 2016), não removíveis por raspagem e localizadas principalmente em borda lateral de língua, podendo ocorrer bilateralmente (VALE et al, 2016). Os estudos sugerem que a leucoplasia pilosa oral é resultante do processo direto de replicação do EBV, sendo assim, não está associada a infecção latente do vírus (GUIDRY et al, 2017).…”
Section: Discussionunclassified
“…In this case, the lesions were found in a patient with a very low CD4+ count. It has been reported that there was a significant relationship between the decreased CD4+ counts and the increased Candida colonization rate and the occurrence of OPC (Das, Saikia, Nath, & Phukan, 2016), or OHL emergence (Chattopadhyay et al., 2005; Vale, Martins, Silva, & Ortega, 2016). The administration of topical Nystatin oral suspension in this patient was changed to fluconazole per oral because the lesion regressed.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers also state that the presence of this lesion could indicate a therapeutic failure or serve as a marker of AIDS progression [ 4 , 7 , 9 , 25 ]. In our case, it was not possible to correlate the presence of OHL with an occasional failure of the treatment because patients with OHL had a viral load of 1.1 log ( P = 0.155), on average, or consider the lesion as a marker of AIDS progression because the correlation between presence of OHL and disease staging was not statistically significant ( P = 0.301).…”
Section: Discussionmentioning
confidence: 99%
“…The histopathological characteristics are not exclusive to this lesion, which may include hyperkeratosis, epithelial hyperplasia, ballooning degeneration, and discrete or even absent inflammatory mononuclear cells infiltrate. For this reason, the criteria used for the final diagnosis of OHL have been always discussed [ 2 , 7 ]. Previous study published by our group showed that among 36 cases of OHL diagnosed in clinical and histopathological basis, only 80.55% were EBV positive, confirming the previous diagnosis [ 8 ].…”
Section: Introductionmentioning
confidence: 99%